2001
DOI: 10.1089/109493101750527079
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality–Based Multidimensional Therapy for the Treatment of Body Image Disturbances in Obesity: A Controlled Study

Abstract: The main goal of this paper is a preliminary evaluation of the efficacy of a virtual reality VR-based multidimensional approach to the treatment of body image attitudes and related constructs. The female obese patients (n = 28) involved in a residential weight control treatment, including low-calorie diet (1,200 kcal/day) and physical training, were randomly assigned either to the VR treatment or to psychonutritional groups based on the cognitive-behavior approach. Patients were administered a battery of outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 53 publications
1
59
0
2
Order By: Relevance
“…Several research groups, such as Riva et al [68][69][70][71][72][73][74][75][76][77] and Perpiñ a et al, [78][79][80] have already developed VR environments for the treatment of body-image disturbances and for assessing the changes obtained. The results of these research groups corroborate the usefulness of VR technology in this field.…”
mentioning
confidence: 99%
“…Several research groups, such as Riva et al [68][69][70][71][72][73][74][75][76][77] and Perpiñ a et al, [78][79][80] have already developed VR environments for the treatment of body-image disturbances and for assessing the changes obtained. The results of these research groups corroborate the usefulness of VR technology in this field.…”
mentioning
confidence: 99%
“…It is even possible to generate a body transfer illusion: Slater substituted the experience of male subjects' own bodies with a life-sized virtual human female body. It is also possible to use VR to improve body image (Riva, Melis, 1997; even in patients with eating disorders (Riva, Bacchetta, Baruffi, 2002; or obesity (Riva, Bacchetta, Baruffi, Molinari, 2001;Dean, Cook, 2009). …”
Section: Therapy: A) Phobias Ptsd Anxiety Disorders Etc B) Rehabmentioning
confidence: 99%
“…VR programs focused on the improvement of body image, body satisfaction and physical acceptance in obese patients and reduction of perfectionisms, body dissatisfaction and negative attitudes towards the body in anorectic patients. A few controlled studies demonstrated the effectiveness of VR in the treatment of eating disorders [88][89][90].…”
Section: Other Applicationsmentioning
confidence: 99%